The insider [videorecording (Blu-Ray)] - Pacino, Al, 1940-; Crowe, Russell, 1964-; Plummer, Christopher; Venora, Diane; Hall, Philip Baker, 1931-2022; Crouse, Lindsay; Mazar, Debi; Tobolowsky, Stephen, 1951-; Feore, Colm, 1958-; McGill, Bruce, 1950-; Gershon, Gina; Gambon, Michael; et al. (Buena Vista Home Entertainment, 2013)
When former tobacco executive Dr. Jeffrey Wigand agrees to blow the whistle on the alleged unethical practices within the industry, and forms an alliance with veteran 60 Minutes producer Lowell Bergman, he starts an all-out war that could cost both men their reputations, and much, much more.